(untitled) (Research, Society and Development, 2020)
Objective: To analyze the knowledge and attitude of adolescents about HPV vaccination. Methodology: This is a descriptive, cross-sectional study. A questionnaire was applied to female adolescents, students from public elementary schools in the city of Fortaleza. The data were organized and analyzed using the statistical program Statistical Package for the Social Sciences (SPSS) version 20.0. Results: It was found that 72 (60%) adolescents had inadequate knowledge, all of them had already heard about HPV and its vaccination, however the adolescents did not know the indication for the HPV vaccine. However, attitude about HPV vaccination was adequate in 112 (93.3%) of those surveyed. As for the association between sociodemographic and sexual variables with knowledge, significant associations were observed that were with race and income. Conclusion: The majority of adolescents have inadequate knowledge and an adequate attitude about the HPV vaccine. Inadequate knowledge is related to non-white color and low income, demonstrating that social vulnerabilities have a negative impact.